Islam Translated: Literature, Conversion and the Arabic Cosmopolis of South and Southeast Asia, by Ronit Ricci. Chicago and London: University of Chicago Press, 2011, 313 pp. - Siti Nuraishah Ahmad (Kajian Malaysia, 2017)
The coming of Islam to South Asia and Southeast Asia has long held the interest of scholars of religion, history and culture around the world. There is an impressive body of work on the Islamisation of these regions, studying its routes and the roles played by traders, missionaries, Sufi brotherhoods and diplomatic emissaries. Lesser known, perhaps, is the role of literary activity such as composing, translating and the public reading of texts, in the spread of Islam in these regions.